Transgenerational Social Stress, Immune Factors, Hormones, and Social Behavior - Murgatroyd, Christopher A.; Babb, Jessica A.; Bradburn, Steven; Carini, Lindsay M.; Beamer, Gillian L.; Nephew, Benjamin C. (Frontiers in Ecology and Evolution, 2016)
A social signal transduction theory of depression has been proposed that states that exposure to social adversity alters the immune response and these changes mediate symptoms of depression such as anhedonia and impairments in social behavior. The exposure of maternal rats to the chronic social stress (CSS) of a male intruder depresses maternal care and impairs social behavior in the F1 and F2 offspring of these dams. The objective of the present study was to characterize basal peripheral levels of several immune factors and related hormone levels in the adult F2 offspring of CSS exposed dams and assess whether changes in these factors are associated with previously reported deficits in allogrooming behavior. CSS decreased acid glycoprotein (α1AGP) and intercellular adhesion molecule-1 (ICAM-1) in F2 females, and increased granulocyte macrophage-colony stimulating factor (GM-CSF) in F2 males. There were also sex dependent changes in IL-18, tissue inhibitors of metalloproteinases 1 (TIMP-1), and vascular endothelial growth factor (VEGF). Progesterone was decreased and alpha melanocyte stimulating hormone (α-MSH) was increased in F2 males, and brain-derived neurotrophic factor (BDNF) was decreased in F2 females. Changes in α1AGP, GM-CSF, progesterone, and α-MSH were correlated with decreased allogrooming in the F2 offspring of stressed dams. These results support the hypothesis that transgenerational social stress affects both the immune system and social behavior, and also support previous studies on the adverse effects of early life stress on immune functioning and stress associated immunological disorders, including the increasing prevalence of asthma. The immune system may represent an important transgenerational etiological factor in disorders which involve social and/or early life stress associated changes in social behavior, such as depression, anxiety, and autism, as well as comorbid immune disorders. Future studies involving immune and/or endocrine assessments and manipulations will address specific questions of function and causation, and may identify novel preventative measures and treatments for the growing number of immune mediated disorders.